Sweetheart [videorecording (DVD)] - Morrison, Marley; Barlow, Nell; Hartley, Jo, 1972-; Smith, Ella-Rae, 1998-; Di Martino, Sophia; Anderson, Samuel, 1982-; Byron, Tabitha (Film Movement series., 2023)
Socially awkward lesbian teenager AJ begrudgingly joins her family on a seaside vacation. She finds herself constantly at odds with her painfully "normal" mother and older sister, neither of whom can understand why she doesn't smile more or "dress like a girl." Her anticipated "week of hell" takes an unexpected turn when Isla, a free-spirited and sun-loving lifeguard, catches her eye.